Implementación de una metodología para controlar la temperatura en el pasteurizador de la planta de lácteos de la UNACH. - Guerrero Rodriguez, Mesias Agusto (2024)
Regarding thermal treatments, temperature and time are crucial for food quality by slowing pathogenic microorganisms' development and preserving nutritional properties. The researcher implemented an automatic control system to manage these variables in the milk pasteurizer at CETTEPS-UNACH. First, it was essential to define the system. Then, 50, 150, and 250 liters of milk were pasteurized, manually controlling the temperature with a digital thermometer. During the holding stage, temperatures between 61 and 67°C were recorded. Due to these values were not adequate, it was essential to implement an automatic control system composed of a Siemens LOGO V8 PLC, a type J thermocouple, three solenoid valves for steam, cold water, and purge flow, and a router for signal transmission and control through the logo web editor application. With this system, temperature variability was controlled and reduced by 86%. When reapplying the thermal treatment to 50, 150, and 250 liters of milk, the temperature during the holding stage ranged between 62.5 and 63°C, remaining within the range established by the literature. However, a variation of up to +/- 0.3°C was allowed due to possible equipment fluctuations. Subsequently, it was confirmed with 99% reliability that there are significant differences between the two methods of controlling temperature by comparing means using the T-student statistical technique. Nonetheless, the difference between the two types of control was corroborated through control charts and in terms of standard deviation and variability.